Tax Planning and Transfer Pricing - Putri, Andiena Nindya (Yayasan Pendidikan Belajar Berdikari, 2024)
The purpose of this research is to examine the influence of tax burden, currency rate, and tax planning on transfer pricing choices made by manufacturing businesses listed on the Indonesian Stock currency between 2019 and 2023. Purposive sampling was used to pick the sample, which was chosen by 12 firms. In this research, employ the double linear regression analysis approach for analysis. According to the findings of this research, tax burden has a favorable influence on transfer pricing, however exchange rate and tax planning have no effect on transfer pricing